Bentuk Integrasi Pemujaan Tri Murti Di Pura Dalem Taak Desa Batubulan Kecamatan Sukawati Kabupaten Gianyar - Supandi, I Nyoman Alit (Jayapangus Press, 2023)
Pura Dalem Taak has its own uniqueness where there is the concept of Tri Murti in it. The concept of the Tri Murti is generally worshiped in certain temples, but in Dalem Taak Temple, the gods Brahma, Vishnu and Shiva become a worship unit that cannot be separated from one another. This happened because of an integration between Dalem Bantas Temple and Dalem Taak Temple. The purpose of this study was to analyze the existence of an integrated form of Tri Murti worship in the Dalem Taak Temple, Batubulan Village, Sukawati District, Gianyar Regency. The type of research used is qualitative using religious theory and structural-functional theory. The data sources in this research are primary data sources and secondary data sources. Primary data sources were obtained through observation and interviews while secondary data sources were obtained through document studies and literature studies. The results of this study are 1) The architecture of the Dalem Taak Temple building has the Tri Mandala, as a medium for developing harmony within the Tri Hita Karana territory. 2) The Pelinggih building ornament at Dalem Taak Temple has its aesthetic value and also has its own symbolic meaning. 3) Upakara or ceremonies are held at Dalem Taak Temple, which is on Kuningan day. The integration of Pura Dalem Taak was carried out thanks to community communication and the Bhujangga Waisnawa clan, previously at Pura Dalam Taak there was one shrine namely Padma Rong Lima, and there were no graves or other shrines yet, Pura Dalem Bantas was moved to Pura Dalem Taak so that it is now a single unit that intact.